EVALUASI TERHADAP IMPLEMENTASI JOB SAFETY ANALYSIS (JSA) DENGAN JOB SAFETY OBSERVATION (JSO) - satria jaya eka putra; Armada Armada (Jurnal TeKLA, 2023)
The implementation of flexible pavement work on the East Riau Crossroads Business Entity Government Cooperation (BEGC) project, which has an active road status, already has a hazard control document. One form of the hazard control document is the Job Safety Analysis (JSA) document. From the results of the analysis of existing JSA documents, hazards and their controls have been identified. To determine the level of compliance in implementing hazard control recommendations in the field, it is necessary to observe the Job Safety Observation (JSO) method, which is a method of observing work to improve the quality of work safety implementation. Based on the results of an evaluation of the implementation of JSA on the BEGC project on the East Riau crossroads using the JSO method, especially in the Trial AC-WWC (wearing-ccourse) work, it can be concluded that of the 32 forms of JSA control carried out in the field, according to the results of the JSO carried out at STA 18+300–18+900, only 20 forms of control (62.5%) were found, and also three forms of hazard control whose form of implementation in the field cannot be ascertained.